2012
DOI: 10.1016/j.molcel.2012.08.022
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 Nuclear Interactome Reveals Key Regulators of Its Transcriptional Activity and Oncogenic Function

Abstract: Activating mutations in NOTCH1, an essential regulator of T cell development, are frequently found in human T cell acute lymphoblastic leukemia (T-ALL). Despite important advances in our understanding of Notch signal transduction, the regulation of Notch functions in the nucleus remains unclear. Using immunoaffinity purification, we identified NOTCH1 nuclear partners in T-ALL cells and showed that, beyond the well-characterized core activation complex (ICN1-CSL-MAML1), NOTCH1 assembles a multifunctional comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
175
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(185 citation statements)
references
References 34 publications
8
175
2
Order By: Relevance
“…A recent study showed that in T-LL cells the chromatin regulators LSD1, PHF8, AF4p12, and BRG1 associate with NTCs on regulatory elements such as the DTX1 and IL7R enhancers, and are required for expression of at least a subset of NOTCH target genes (31). An additional finding of our work is the strong correlation between the occupancy of dynamic NOTCH1-binding sites and levels of H3K27 acetylation of Notch response elements and associated target gene promoters.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A recent study showed that in T-LL cells the chromatin regulators LSD1, PHF8, AF4p12, and BRG1 associate with NTCs on regulatory elements such as the DTX1 and IL7R enhancers, and are required for expression of at least a subset of NOTCH target genes (31). An additional finding of our work is the strong correlation between the occupancy of dynamic NOTCH1-binding sites and levels of H3K27 acetylation of Notch response elements and associated target gene promoters.…”
Section: Discussionsupporting
confidence: 67%
“…Runx factors also recruit p300 to chromatin, and it is possible that optimal recruitment of p300 to Notch response elements such as the IL7R enhancers requires both Notch and Runx factors. Of note, Yatim et al identified RUNX1 as a component of the NOTCH1 interactome in T-LL cells (31), raising the possibility that NOTCH1 and RUNX1 might physically contact each other on genomic response elements; however, dynamic NOTCH1 sites and nearby RUNX1 sites do not show any preferred spacing in T-LL genomes, making direct physical interaction unlikely as a general rule. Further work will be needed to define the basis and extent of Notch/Runx transcriptional interplay in T-LL cells and normal hematopoietic progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that removal of RBPJ/Su(H) in the absence of NICD results in the transient activation (derepression) of some target genes (Morel and Schweisguth 2000;Koelzer and Klein 2003;Mulligan et al 2011;Yatim et al 2012). Our observation that RBPJ occupancy is strongly reduced at the inducible sites under Notch-off conditions prompted us to measure directly the repressive function of endogenous RBPJ in primary myogenic cells.…”
Section: Active Repression By Rbpj Does Not Occur On a Subset Of Itsmentioning
confidence: 93%
“…In the first class, RBPJ is dynamically recruited to its targets together with the cleaved intracellular domain of Notch and p300. This inducible behavior of RBPJ controverts the classical view of static RBPJ binding to DNA (Barolo et al 2002;Bray 2006), a view that was further reinforced recently in human T-cell lymphoblastic cells (Yatim et al 2012). This dynamic property has been also attributed to Su(H) (fly RBPJ) for five enhancer elements of the E(spl) cluster (Krejci and Bray 2007) yet has not been clearly demonstrated in mammalian cells or on a whole-genome scale.…”
mentioning
confidence: 89%
“…Upon activation through cell-to-cell interaction, the Notch intracellular domain is released from the cell membrane and translocates to the nucleus, where it initiates the formation of a ternary complex with Maml and CSL (3,4). It is thought that this ternary complex serves as a scaffold to recruit additional transcriptional coactivators to drive a Notch-dependent transcriptional cascade (5)(6)(7)(8). Therefore, deregulation of Notch leads to the aberrant enforcement of a transcriptional profile that drives a neoplastic program (3,4,9,10).…”
Section: Introductionmentioning
confidence: 99%